ANALYSIS OF THE READING ABILITY OF THE QUR'AN OF UIN AR-RANIRY ISLAMIC RELIGIOUS EDUCATION STUDY PROGRAM THROUGH MAQRA TAHSIN AL-QUR'AN - Faiz, Muhammad; Jailani (Al-Mubin, 2025)
This study aims to analyze the level of mastery of Qur'an reading by students of the Islamic Religious Education Study Program (PAI) UIN Ar-Raniry Banda Aceh using the maqra tahsin method. The focus of the research includes three main aspects: (1) the ability to apply tajweed, (2) the understanding of tahsin reading, and (3) the influence of educational background on Qur'anic reading competence. The research uses a descriptive quantitative method with a data collection technique through direct tests using validated maqra tahsin instruments. The research sample consisted of 40 students of the class of 2021 who were selected by purposive sampling, representing four categories of educational backgrounds: tahfiz Islamic boarding schools, non-tahfiz Islamic boarding schools, aliyah madrasas, and public schools. The results of the study showed that overall, PAI UIN Ar-Raniry students had the ability to read the Qur'an with an average score of 161.25 (category B). Comparative analysis revealed significant differences based on educational background, where students graduating from tahfiz Islamic boarding schools obtained the highest scores (188.2), followed by non-tahfiz boarding schools (182.7), aliyah madrasah (171.6), and public schools (155.7). Another important finding is the weakness in mastering gharib recitation (especially imalah, saktah, and naql) and fawatihu suwar in students with public school backgrounds. Based on these findings, this study recommends several improvement strategies, including: (1) an intensive coaching program based on campus ma'had, (2) the development of structured tahsin learning modules, (3) an integrated remedial system, and (4) a more comprehensive integration of the tahsin curriculum. The implications of this research are not only important for improving the quality of learning in the PAI Study Program, but also as a basis for the development of a more inclusive Islamic education policy